Pengelolaan Badan Layanan Umum Daerah dalam Mewujudkan Lulusan Unggul SMKN 6 Yogyakarta - Selawati, Fajar; Mundilarno (Media Manajemen Pendidikan, 2025)
This research aims to: 1) realize superior graduates at SMKN 6 Yogyakarta through BLUD (Regional Public Service Agency) management; 2) analyze the supporting and inhibiting factors in achieving this goal; and 3) evaluate the success of BLUD management in producing excellent graduates. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The data analysis process involved data collection, reduction, presentation, and conclusion drawing. The findings indicate that BLUD management effectively fosters entrepreneurial skills, work experience, leadership spirit, and students’ confidence in independent work practices. Supporting factors include the availability of competent human resources, strong local government support in regulatory matters, and the principal's creative and innovative leadership style. Inhibiting factors involve the need for continuous improvement in student character development to meet industry standards and the limited marketing promotion, which restricts product and service outreach primarily to specific groups. The success of BLUD management is reflected in the achievements of SMK students, evidenced by numerous awards won in various competitions, showcasing the effectiveness of the program in producing superior, industry-ready graduates.